2014
DOI: 10.1002/eji.201344300
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of innate immune activation accelerates Th1‐cell priming and protection following pulmonary mycobacterial infection

Abstract: The immune mechanisms underlying delayed induction of Th1-type immunity in the lungs following pulmonary mycobacterial infection remain poorly understood. We have herein investigated the underlying immune mechanisms for such delayed responses and whether a selected innate immune-modulating strategy can accelerate Th1-type responses. We have found that, in the early stage of pulmonary infection with attenuated Mycobacterium tuberculosis (M.tb H37Ra), the levels of infection in the lung continue to increase loga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…In contrast, delivery of FimH, a TLR4 ligand, improved T-cell responses and resulted in ∼1 log reduction in lung bacterial burden, following high-dose intranasal infection with Mtb H37Ra (ref. 53). To our knowledge, no published studies have manipulated early host responses in vaccinated Mtb -infected hosts, with resulting complete early Mtb control.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, delivery of FimH, a TLR4 ligand, improved T-cell responses and resulted in ∼1 log reduction in lung bacterial burden, following high-dose intranasal infection with Mtb H37Ra (ref. 53). To our knowledge, no published studies have manipulated early host responses in vaccinated Mtb -infected hosts, with resulting complete early Mtb control.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have previously demonstrated that the inoculation of pro-inflammatory agonists, such as Toll-like receptor ligands, into the lung of intramuscularly immunised animals is able to draw antigen-specific T-cells from the peripheral sites into the airway lumen and provide protection against pulmonary TB [5,14]. Furthermore, we have recently demonstrated that a robust innate inflammatory response is key for the timely generation of anti-TB T-cell immunity in the lung following primary pulmonary M. tuberculosis infection [10].…”
Section: Effect Of Local Pro-inflammatory Signals On the Distributionmentioning
confidence: 91%
“…Upon exposure to M. tuberculosis, the bacterium is deposited into the lung airway, and infects local macrophage and dendritic cells. After 8-9 days these cells migrate to the lung draining lymph node, where they prime naïve T-cells and provide the activation signals to generate a population of M. tuberculosis-specific T-cells [10]. These cells then travel through the lymphatic circulation into the venous blood circulation, eventually ending up in the pulmonary vasculature (pulmonary artery).…”
Section: Protection Against Pulmonary Tb Is Determined By the Differementioning
confidence: 99%
“…By Day Dr. Zhou Xing described vaccination strategies to elicit enhanced protective immunity on the respiratory mucosal surface that will provide a more rapid immunological response to infection. Following Mtb infection of naïve mice, bacteria replicate rapidly in the lungs during the first 14 days of infection, and only begin to slow down when the adaptive immune response begins around 21 days post-infection [61][62][63]. Even animals that have received subcutaneous BCG vaccination demonstrate a delayed airway CD-4+ T-cell response, which only begins 14 days after the Mtb challenge, too late to protect against the initial rapid bacterial build up.…”
Section: Aerosol Bcg Vaccine Dr Peter Beverley Nuffield Departmentmentioning
confidence: 96%